Diffusion MR imaging acquisition and analytics for microstructural delineation in pre‐clinical models of TBI. Issue 5 (1st May 2019) - Harris, N. G.; Paydar, A.; Smith, G. S.; Lepore, S.
Abstract: Significant progress has been made toward improving both the acquisition of clinical diffusion‐weighted imaging (DWI) data and its analysis in the uninjured brain, through various techniques including a large number of model‐based solutions that have been proposed to fit for multiple tissue compartments, and multiple fibers per voxel. While some of these techniques have been applied to clinical traumatic brain injury (TBI) research, the majority of these technological enhancements have yet to be fully implemented in the preclinical arena of TBI animal model‐based research. In this review, we describe the requirement for preclinical, MRI‐based efforts to provide systematic confirmation of the applicability of some of these models as indicators of tissue pathology within the injured brain. We review how current DWI techniques are currently being used in animal TBI models, and describe how both acquisition and analytic techniques could be extended to leverage the progress made in clinical work. Finally, we highlight remaining gaps in the preclinical pipeline from data acquisition to final analysis that currently have no real, preclinical‐based correlate.